Effects of pregnancy and post-kidding stages on haematochemical parameters in cross-bred goats. Issue 1 (1st January 2018) - Cepeda-Palacios, Ramón; Fuente-Gómez, Mayra Guadalupe; Ramírez-Orduña, Juan Manuel; García-Álvarez, Abril; Llinas-Cervantes, Ximena; Angulo, Carlos
ABSTRACT: The effects of pregnancy and post-kidding stages, and the number of in utero developing foetuses on haematochemical parameters were evaluated in stabled cross-bred goats. Blood serum samples were collected biweekly during the late-pregnancy (–49 days) and post-kidding stages (21 days) ( n = 34 goats, including 17 Anglonubian and 17 Saanen × Anglonubian). Non-pregnant, cross-bred, adult does ( n = 17) were used as controls. Blood serum glucose (GL), total protein (TP), albumin (AL), uric acid (UA), total cholesterol (TC), total bilirubin (TB), creatinine (CR), and alkaline phosphatase (AP) were measured using commercial kits. Average GL, TP, AL, and AP values were found to be different ( p < .05) in pregnant, control, and post-kidding stages. Average GL level was found to be different ( p < .05) in Anglonubian vs. Saanen×Anglonubian goats. Number of developing foetuses had no effect on any measured haematochemical parameters. In conclusion, both the late pregnancy and post-kidding stages of Anglonubian and Saanen × Anglonubian goats were accompanied by changes in blood serum GL, TP, AL, and AP. Breed effect was only observed on serum GL, while number of kids developing in utero did not affect the measured haematochemical parameters of goats.